2011
DOI: 10.1111/j.1708-8208.2011.00362.x
|View full text |Cite
|
Sign up to set email alerts
|

A Hydrophilic Dental Implant Surface Exhibit Thrombogenic Properties In Vitro

Abstract: The conclusion that can be drawn from the results in our study is that the hydrophilic modification seems to augment the thrombogenic properties of titanium with implications for healing into bone of, that is titanium dental implants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 42 publications
4
34
0
1
Order By: Relevance
“…72 ± 3° [46]), which influences thrombogenicity [47]. This emphasizes furthermore the importance of the scaffold topography in thrombogenicity of the construct.…”
Section: Discussionmentioning
confidence: 89%
“…72 ± 3° [46]), which influences thrombogenicity [47]. This emphasizes furthermore the importance of the scaffold topography in thrombogenicity of the construct.…”
Section: Discussionmentioning
confidence: 89%
“…This process is mainly initiated by platelet activation (release of cytokines, growth factors) within the fi rst 3 days of healing [ 32 , 35 ]. In this context, it was demonstrated that whole blood collected from human patients in direct contact with modSLA surfaces revealed signifi cantly increased degrees of platelet binding, platelet activation, and intrinsic coagulation system activation, when compared to SLA surfaces [ 111 ]. The activated platelets not only stimulate factors that enhance osteogenetic cells but also release factors that activate leukocytes and macrophages (between 24 and 48 h after implant placement), which are involved in the demolition of the peri-implant blood clot [ 35 ], thus probably delaying the healing process.…”
Section: Modsla: Bone Tissue Healing and Remodelingmentioning
confidence: 99%
“…2,3 Although there are in vitro animal and human studies reporting that modifications on MRCM implant surface induce a fast, secure and predictable response in bone apposition, it is not sufficiently clear whether this effect is caused due to roughness, surface chemistry or changes in both properties. [43][44][45][46] While some studies indicate that modifications introduced in MRCM surface production have no structural impact and do not promote differences in topography, 18,19,39,47 some studies 45,48 yielded different results regarding roughness parameters (Sa and Sdr) for MR and MRCM surfaces. Nanometric differences between the new surface and its predecessor were also reported.…”
Section: Discussionmentioning
confidence: 99%